Some aspects of the transmission mechanism (2007)
A common allegation is that monetary economics lacks a theoretically integrated and empirically plausible account of ‘the transmission mechanism’, where the transmission mechanism is the process (or set of processes) by which changes in the quantity of money lead to changes in national income.1 As monetarism would be incomplete without a transmission mechanism, this allegation would be serious if it were true. In fact, monetary economics has a simple and persuasive body of ideas which relates the quantity of money to asset prices and national income, and which has been passed down through successive generations of teachers and students at some universities, although certainly not all. (In one case the ideas formed the celebrated ‘oral tradition’ of Chicago monetary economics.2) However, monetary economics is no longer taught with much rigour in most British universities and the transmission mechanism from money to the economy is undoubtedly a mystery to many British economists.